2022
DOI: 10.1186/s12877-022-03343-6
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and malnutrition are associated with other geriatric syndromes and increase risk for 30-Day readmission in hospitalized older adults: a prospective cohort study

Abstract: Background Readmission in older adults is typically complex with multiple contributing factors. We aim to examine how two prevalent and potentially modifiable geriatric conditions – depressive symptoms and malnutrition – relate to other geriatric syndromes and 30-day readmission in hospitalized older adults. Methods Consecutive admissions of patients ≥ 65 years to a general medical department were recruited over 16 months. Patients were screened fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
2
4
0
Order By: Relevance
“…The proportion of the older people with poor dietary intake in the pre‐implementation group was similar to that of a previous local study by Laura et al. (2022). However, a reduction in the proportion of older people with poor dietary intake, and the increase in total meal and protein intake were observed, despite the post‐implementation group being older, and more likely to present with nutritional risk factors.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The proportion of the older people with poor dietary intake in the pre‐implementation group was similar to that of a previous local study by Laura et al. (2022). However, a reduction in the proportion of older people with poor dietary intake, and the increase in total meal and protein intake were observed, despite the post‐implementation group being older, and more likely to present with nutritional risk factors.…”
Section: Discussionsupporting
confidence: 88%
“…This QI project demonstrated that a nurse-driven mealtime assistance bundle may improve the dietary intake of hospitalised older people who are at risk of malnutrition. The proportion of the older people with poor dietary intake in the pre-implementation group was similar to that of a previous local study by Laura et al (2022).…”
Section: Discussionsupporting
confidence: 85%
“…We screened 14,006 abstracts and 2287 full texts, from which 45 cohorts (n = 39,041,266 admissions, 49 publications) 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 were eligible for inclusion ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Third, multiple association studies were conducted on the variables. Directed acyclic graphs (DAGs) were used to initially select potential influencing factors (Laura et al, 2022), and based on that, mediators were excluded. The ICCs measure the degree of clustering of three essential aspects (ESBG, Schneiderian membrane perforation and implant survival) and were 0.438, 0.314 and 0.681, respectively.…”
Section: Methodsmentioning
confidence: 99%